Kesalahpahaman Makna Gugatan Perwakilan Kelompokdan Legal Standing di Indonesia - Machsun Tabroni (Jurnal Hukum IUS QUIA IUSTUM, 2004)
A long side conventional civil suits, the development of the civil law of procedure_ hasled to the emergence of class action and legal standing. A class action is filed by one or more --persons in the irown interests, butal soon be half of and in the interests ofa large group of people; where as legal standing is merelyan "entrance tickef to the legal battle whichhas many obstacles. Among others, these obstacles include evidence of proof the remedial tools available, and even the obstacle ofthe readiness of the council of Judges to make the best decision.